До історії співпраці І.Крип’якевича з «Українським історичним журналом» - Заболотна, І.М. (Український історичний журнал, 2015)
Розглядається участь академіка І.Крип’якевича в організації й діяльності єдиного в УРСР історичного часопису. Висвітлюється період становлення журналу в умовах суспільного-політичного життя кінця 1950-х рр. Розкриваються особисті та офіційні взаємини І.Крип’якевича з відповідальним редактором «УІЖ» – Ф.Шевченком. The article deals with participate in organization and activities of “Ukrainian Historical Journal” of academician I.Krypiakevych. Reflected scientists vision of the magazine concept. Are called areas of his research published in the journal. The article sheds light on the initial period of organization and activities of “UHJ” in terms of the then social and political life. Revealed features of personal and official relations of I.Krypiakevych with the managing editor of journal F.Shevchenko.